INTERMITTENT FASTING: LITERATURE REVIEW WITH BIBLIOMETRIC ANALYSIS - Hordiienko, Hanna; Sikora, Vitalii (Eastern Ukrainian Medical Journal, 2025)
Introduction. Intermittent fasting is a dietary approach that has gained phenomenal popularity in the last decade. Unlike traditional calorie restriction or restriction of certain foods, it is based on limiting the time during which food can be consumed.The aim of the work was to conduct a literature review with bibliometric analysis of scientific articles on the topic of intermittent fasting.Materials and methods. The authors searched the literature sources in the database using the keyword “intermittent fasting”. The built-in elements of the bibliometric analysis of the Scopus database and the VOSviewer program (version 1.6.20, https://www.vosviewer.com/) were used to analyse the quantitative and qualitative characteristics of the publications.Results. Between 1946 and 2025, 3056 publications were published in the Scopus database with the keyword “intermittent fasting”, and their number has increased significantly over the past 10 years. During the bibliometric analysis of publications by the most common keywords, it was found that the most frequently encountered words together with the phrase “intermittent fasting” were such words as “diet”, “physiology”, “obesity”, “metabolism”, “body weight”, and “animal models”.Conclusions. Intermittent fasting is characterised by a complex effect on the human body: it improves insulin sensitivity, stimulates autophagy, and regulates circadian rhythms. Intermittent fasting has a significant impact on body weight loss and may also reduce the risk of cardiovascular disease, as well as improve cognitive function. Despite the large body of research on the benefits of intermittent fasting, its safety remains questionable. Further long-term studies of this dietary approach in animal models and human populations are needed.